Future is urban livability, resilience & resource conservation : proceedings of the International Conference on Future is Urban (ICFU 21), December 16-18, 2021, Ahmedabad, India - International Conference on Future is Urban (2021 : Ahmedabad, India); Sharma, Utpal; Parthasarathy, R.; Aparna ([S.l.] : ROUTLEDGE, 2022)
Cities have played an important role in our lives since the dawn of civilization. However, cities are slowly becoming overwhelmed and therefore intervention is desirable towards green, blue and egalitarian nature. Even with current urban issues, we must rise to the occasion as professionals to create cities that are social, cities that take care of the environment, and cities that are digital. Increased citizen participation is indispensable in this process. The International Conference on Future is Urban (IFCU' 21) Dec 16-18, 2021, Ahmedabad, India', takes into account Livability, Resilience & Resource Conservation for planning Future and cities in future.
Keywords: POLITICAL SCIENCE / Public Policy / Environmental Policy; POLITICAL SCIENCE / Public Policy / City Planning & Urban Development; Cities and towns -- Congresses